(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The aim of this research is to identify the role and effectiveness of the social specialist in the schools in Damascus city and its countryside, the status of school problems, and the obstacles to social service at schools. To achieve this goal, field visits and individual interviews were conducted at a sample of 10 schools to obtain real information about the role and effectiveness of social service in schools. The study found that the social specialists at schools are inefficient and do not perform their duties as required. The research also found that school problems (health, educational, social and behavioral) need to be classified and studied in order to find solutions. The study also found that there are obstacles to social services, such as the lack of confidence in the role of the social services in problem solution, lack of cooperation between the administration and parents, lack of qualification and training for the social specialist to reach the required level. These obstacles should be addressed and overcome.